MEMBANGUN DIGITAL MARKETING YANG EFEKTIF PADA PRODUK LOKAL (su-re.co) - Emilika Budi Lestari; Ngurah Adhi Santosa; Ni Ketut Netri Andiyani (Jurnal Nawala Visual, 2021)
In digital marketing on social media the role of layout in digital marketing on social media plays an important aspect but not in su-re.co. However, su-re.co has not implemented a good layout, yet. This is because the layout of Instagram feeds has not arranged properly, because the company's content combines with activities, product sales, and video testimonials. Therefore, the author uses qualitative method, which is a method that examines the problem in case of case. In addition, the author provides a graphic design theory for a digital marketing. This theory will explain in detail what design theory is right to use. For the results of their own research, the authors found several sample feeds for social media content that could be applied. This aims to further develop creative ideas in designing a digital marketing on su-re.co and can be known by everyone with interesting visuals, simple, unique and varied both in providing content and explanation of activities by the company for the natures and the farmers in Indonesia.